Case report: Clinicopathological and molecular characteristics of pediatric-type follicular lymphoma - Ren, Beibei; Chen, Yu; Bai, Xuanye; Zheng, Jiawen; Chang, Jing; Jiang, Xiangnan; Xia, Qingxin; Zhang, He (Frontiers in Pediatrics, 2023)
Pediatric-type follicular lymphoma (PTFL) is one of the rare pediatric-type indolent B-cell lymphomas that clinicopathologically differs from adult lymphoma. Accurate diagnosis of PTFL, which is often challenging, is essential to avoid missed-diagnosis, misdiagnosis and overtreatment.To improve our understanding of PTFL, clinicopathological features, differential diagnosis and molecular mutation characteristics of four cases of PTFL were analyzed using hematoxylin and eosin staining, immunohistochemistry, polymerase chain reaction, fluorescence in situ hybridization (FISH) and next-generation sequencing (NGS). The relevant literature review was also performed. Four PTFL patients were all male, aged 6, 18, 13 and 15 years and had St. Jude stage I or III. Microscopic results showed that the lymph node structure was destroyed; the tumor follicles were enlarged and 1 †These authors contributed equally to this work and share last authorship.2 irregular; medium-large blastoid cells with a consistent shape were visible in tumor follicles, and the nucleus was round or oval; and the "starry sky" pattern was easily discovered. Tumor cells expressed CD20, PAX-5, BCL6 and CD10. None of the tumor cells expressed BCL2, CD3, CD5, MUM1 and CyclinD1. CD21 showed dilated growth of a follicular dendritic cell network in tumor follicles.EBER genes were negative in all cases. FISH testing also showed negative BCL2 gene breaks and IRF4 gene breaks in all cases. Twelve related mutant genes, including KMT2D, CD79B, GNA13, MYD88, PCLO, TCF3, IRF8, MAP2K1, FOXO1, POLE, INPP5D and FAT4, were detected by NGS.Two of the four cases had an IRF8 gene mutation and one case had a dual mutation of the MAP2K1 gene. Our study revealed the unique clinicopathological features and molecular mutational characteristics of PTFL, consolidated our understanding of PTFL and identified other rare mutant genes, which may further contribute to the study of the molecular mechanism and differential diagnosis of PTFL.